The Impact of Culture on the Management Values and Beliefs of Korean Firms - Song, Young; Meek, Christopher (Journal of Comparative International Management, 1998)
Korea has become the object of growing international interest among scholars and practitioners because of its remarkable economic achievement in the past three decades. However, the relationship between corporate management practice and Korean cultural values has received only limited attention. This paper claims that studying espoused values and beliefs of firms should be the first step to understanding the impact of national culture on management practices. The paper first outlines several important aspects of Korean culture and them examines their impact on management values and beliefs. Next, it analyzes the contents of the management values and beliefs by examining two organizational symbols--company motto and company song. Finally, the paper discusses how management values and beliefs impact on human resource management policies and practices. The paper concludes that the Korean core cultural values of harmony, unity, and vertical social relations strongly influence Korean firms, and that these management values and beliefs play a profound role in shaping human resource practices.